Public Perceptions Towards Belt and Road Initiative (BRI) in MalaysiaPublic Perceptions Towards Belt and Road Initiative (BRI) in Malaysia - Hassan, Nor Azlili; Ismail, Mohd Mahadee; Abdullah, Azlina; Yunus, Marzudi Md; Din, Hairol Anuar Mak (International Journal of Psychosocial Rehabilitation, 2020)
News media plays an important role in strengthening a diplomacy relations or friendship between countries. As such, Belt and Road Initiative (BRI) is a symbol of diplomatic relations between Malaysia and China. Hence, when dealing with diplomatic relations, a question of how the media portrays the messages of their countries’ communities is the major concerns of this study. This paper attempts to explain the public perception in the Malay newspapers towards BRI in Malaysia. The news coverage of Malaysia-China relationships on BRI is examined comparatively across the two Malay prominent newspapers, namely Berita Harian and Utusan Malaysia, in different perceptions, namely positive, moderate or mix and negative perceptions. By employing framing of the content analysis as the research method, this study obtained 95 news items from Utusan Malaysia and Berita Harian between 1 April 2018 and 31 December 2018. The results revealed that, the Malaysia-China relationships was characterized by a positive perception towards Malaysia and China that described bilateral relations. The economic consequences and responsibility frame were most highlighted by the Malay newspapers. Notably, this study found that these two newspapers were mostly positive and moderate to portray their respective governments. Therefore, the main perceptions and trend of the Malay newspapers is positive and moderate thus the Malaysian communities have a relatively good perception on BRI.